Exclusive Breastfeeding Behavior Analysis at Hospital in Lampung Indonesia - Erlina Puspitaloka Mahadewi; Intan Silviana Mustikawati; Mohamad Reza Hilmy; Ade Heryana (Publisher Cv. Inara, 2021)
The present study reports the comprehensive study on the exclusive breastfeeding around support factors for successful activityof breastfeeding. In the three years lately UNICEF and WHO data on exclusive breastfeeding can reduce infant morbidity and mortality by more than 80%. The coverage of infants who are exclusively breastfed is 65.35%, the highest percentage is in West Nusa Tenggara 80.35% and the lowest percentage is in Papua 18.32%. In Indonesia, there are 35.25% of 38% of children who are sick because they cannot receive exclusive breastfeeding. Exclusive breastfeeding is given when the baby is born until the age of 6 months. This study aims to determine knowledge, work and family support related to exclusive breastfeeding behavior in the work area of ??near with the RSIA PBH hospital in Lampung, Indonesia area in 2021. Using a cross sectional, a large sample of 120 respondents. Sampling in this study used a simple random sampling technique, and the chi-square test was carried out from January to August 2021. The results of the study were 95 respondents (79,16%) mothers who did not give exclusive breastfeeding and 25 respondents (20.84%) mothers who have exclusively breastfed their babies. There is a significant relationship between knowledge (P = 0.000 and PR = 1.588), occupation (P = 0.000 and PR = 1.995) and family support (P = 0.001 and PR = 1.514) with exclusive breastfeeding behavior in the patients inside hospital work area in 2021. The paper presents the characterization support from the company, hospital and the closest family for exclusive breastfeeding is also very important. Based on the results of the study, it is recommended that health workers make innovations and new programs to increase exclusive breastfeeding